The use of monthly egg production records for genetic evaluation of laying hens - A Anang; M Mielenz; L Schuler; Rachmat Preisinger (Jurnal Ilmu Ternak dan Veteriner, 2001)
This research addresses the possibilities of using monthly production records for genetic evaluation of laying hens with four different models and different data sets. The data were collected from a pure line of Lohmann Tierzucht GmbH at Cuxhaven in Germany for two generations from 1998 to 1999 with pedigree being traced back one generation. In total of 9735 hens from 220 sires and 1879 dams were analysed. The evaluated models were: (1) Cumulative Model (CM), (2) Multiple Trait Model (MTM), (3) Fixed Regression Model (FRM), and Random Regression Model (RRM). Variance components were estimated using Animal Model with REML and breeding values were predicted using BLUP Animal Model. The RRM is an interesting model for the evaluation. The RRM agrees with the laying curve over the whole evaluated period from the first to eleventh month production. Selection for an increased total production based on the first six month production with the RRM may not be useful. The integration of full year performance from the parent in a selection on the first six month production with the RRM improved the shape of the curve and increased the correlation with the full performance considerably. In addition, genetic evaluation of total production based on odd month production is sufficient for an efficiency of recording system.   Key words: Laying hens, cumulative model, multiple trait model, fixed regression model, random regression model